Assessment of developing-country urban consumers’ willingness to pay for quality of leafy vegetables: The case of middle and high income consumers in Nairobi - Ngigi, M.W; Okello, J. J; Lagerkvist, C.; Karanja, N; Mburu, J. (My University, 2010)
The improvement in income in developing countries has led to emergence of middle and high income consumers in urban centers. Improvement in income usually causes the shift to consumption of non-staples including leafy vegetables. Thus in major developing country urban centers there has been rapid expansion of the grocery sections featuring leafy vegetables in leading retail stores. Specialty stores have also emerged featuring broad range vegetables. Many middle and high income consumers shop these stores. This study examines the willing of the middle and high income consumers who shop specialized stores to pay for quality of leafy vegetables and drivers of willingness to pay for quality. The study uses contingent valuation and the payment card method in eliciting consumers’ WTP. It considers a broad range of quality attributes including safety, nutrition, environmental friendliness, hygiene in handling. The study finds that mean willingness to pay for quality is higher among high income consumers (>60%). It also finds that income, age of children the consumer has, access to information of food safety are among the significant drivers of kale consumers’ willingness to pay for quality of kales. The study concludes that there is demand for quality of leafy vegetables and discusses policy implications
Keywords: Willingness to pay; Food safety; Urban consumers; Leafy vegetables; Kenya